Enhancing sleep, wakefulness, and cognition with transcranial photobiomodulation: a systematic review - Gaggi, Naomi L.; Parincu, Zamfira; Peterson, Anna; O’Brien, Courtney; Kam, Korey; Tural, Umit; Ayappa, Indu; Varga, Andrew W.; Iosifescu, Dan V.; Osorio, Ricardo S. (Frontiers in Behavioral Neuroscience, 2025)
Disruptions in sleep are common across clinical populations, particularly those with neurological and psychiatric disorders, making restorative sleep and sustained wakefulness a public health priority. Sleep is essential for brain function, impacting cognition in addition to serving as a critical factor in memory consolidation and healthy aging. Neuromodulation via transcranial photobiomodulation (t-PBM) increases cerebral mitochondrial activity and blood flow. These effects may underlie improvements in sleep quality and wakefulness observed after t-PBM. In this systematic review, we summarize the current literature across clinical and healthy populations, which describes t-PBM’s potential to improve sleep, wakefulness, and cognition. The scope of this review also includes t-PBM’s effect on the brain’s glymphatic system and blood flow, the potential of this strategy to augment alertness, wakefulness, and associated cognitive processes, and the suggestion for targeted t-PBM application for future research based on the underlying neurobiological mechanisms of t-PBM and wakefulness across diverse clinical populations.